Weekly Patterns in Japanese Stock Returns - Kato, Kiyoshi (Management Science, 1990)
This study investigates the day of the week effect in the Japanese stock returns. Low Tuesday and high Wednesday returns are observed. Most of the positive returns arise during the nontrading period. The Monday effect is also observed in the week whose previous week is closed by Friday trading. Low Tuesday returns appear to be related to low Monday returns in the U.S. The weekly pattern is more pronounced for the returns of smaller firms. A reverse size effect is observed during the trading period.